2003
DOI: 10.1007/bf02719380
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for pulmonary metastases from colorectal cancer

Abstract: Before thoracotomy for pulmonary metastases from colorectal cancer, the serum CEA level was the most useful prognostic factor. Patients with elevated serum CEA level should undergo a careful prethoracotomy systemic survey and postthoracotomy follow-up for extrathoracic metastases, in particular brain metastases, and an appropriate combined therapeutic modality should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 24 publications
2
15
2
Order By: Relevance
“…In addition, the present result is supported by previous reports of the prognosis in patients with pulmonary metastasis from CRC by several investigators [3, 7, 8]. One study showed that patients with a high level of prethoracotomy serum CEA had a more frequent recurrence in extrathoracic sites, especially the brain [11]. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, the present result is supported by previous reports of the prognosis in patients with pulmonary metastasis from CRC by several investigators [3, 7, 8]. One study showed that patients with a high level of prethoracotomy serum CEA had a more frequent recurrence in extrathoracic sites, especially the brain [11]. …”
Section: Discussionsupporting
confidence: 81%
“…Surgical resection for pulmonary metastasis is an effective treatment for patients with pulmonary metastasis from CRC, and previous studies have suggested several prognostic factors affecting survival after a resection of pulmonary metastasis from CRC [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. However, there are discrepancies between the results of these studies.…”
Section: Introductioncontrasting
confidence: 48%
See 2 more Smart Citations
“…In addition, the present case had a normal serum CEA level, solitary pulmonary metastasis and no intrathoracic nodal metastasis, which are favorable prognostic factors revealed in previous studies [9, 10, 11]. Thus, the only factor to predict a poor prognosis in the case was her elevated CTC count (6 CTCs/7.5 ml peripheral blood), which was consistent with a study showing that an elevated CTC count (3 or more CTCs/7.5 ml) was an independent and significant prognostic factor for shorter survival [7].…”
Section: Discussionsupporting
confidence: 75%